As cirurgias espirituais no contexto espírita paulista e a edificação hospitalar do Instituto Medicina do Além - Ferreira, Sérgio Baetta (2020)
Health treatments performed with doctrinal assimilation, the imposition of hands and magnetized water play a central role in spiritism and are recommended by the spiritist Federations to the affiliated centers. Regarding the spiritist therapeutics, there are also "spiritual or mediumistic surgeries", which are considered controversial in the spiritist scenario due to the questionable trajectory of some of the people dedicated to it and the accusations of charlatanism associated with such practice. This dissertation highlights the activities carried out at the Instituto de Medicina do Além (IMA), which is headed by the medium João Berbel. The institution located in the city of Franca, countryside of São Paulo, performs mediumistic surgery and, besides making it clear that this practice is complementary to the traditional medicine, they are also building a conventional hospital. Thus, this research analyzes the leaders’ guidelines in São Paulo’s spiritist partition, which is linked to the União das Sociedades Espíritas (USE) and to the Associação Médico-Espírita, about the practice of spiritual surgery performed by the medium João Berbel and investigates how the process of institutionalization of the Hospital of Charity can re-signify the dilemma that permeates this practice. We seek to understand how the Spiritist movement sees the spiritual surgery, especially highlighting the degree of acceptance and rejection of this practice. A fieldwork was carried out at the Instituto de Medicina do Além (IMA), between 2017 and 2020. To achieve the goals of this research, in addition to the fieldwork, we summarized the most important mediums of the 20th century and explained how the practice of surgery became a controversy in the Spiritist milieu. We based our studies on the Weberian theory of rationalization of the spheres of value (WEBER, 1982, 2000b) - in this case, the religious one - and the theory developed by Pierre Bourdieu on the notion of field and religious work (BOURDIEU, 1984). We investigate how the "mediumistic surgery" is performed by João Berbel – the medium ahead of the IMA. We examine the speeches that refer to the acceptance or rejection of this practice in the Spiritist milieu and if there is resistance how people demonstrate it; moreover, we show how these leaders see the construction of the hospital; finally, we seek to understand how the interaction between spiritual treatments and palliative medicine happens and what are the difficulties faced by the institution to consolidate the hospital project. The field research revealed a certain dilemma in the Spiritist milieu regarding the ‘surgical’ practice, on one hand the statement of the members of USE points to a certain reservation with regard to the practice, especially due to the idea of karma, on the other hand the AME leaders do not mention the notion of karma and its members recognize the practice as a recommendable complementary therapy. In addition to that, the medical professionals who work together with the president of the AME-Regional Franca in the implementation of the hospital unit, reinforce the recognition of the practice in the Spiritist religious field.